Lucid Existenz During Dreaming - Globus, Gordon (International Journal of Dream Research, 2019)
Abstract: In waking Existenz (pace Heidegger) we always find ourselves already thrown amidst the world, whereas in lucid dream Existenz there is this remarkable difference: we actually throw the world. The operation of intentionality—the brain’s self-tuning capability—is discussed with respect to its role in lucid world throwing. The ability to throw authentic worlds while lucidly dreaming raises doubts about the seeming transcendence of world during waking and opens the monadological possibility that we actually throw the world during waking too. To appropriate Freud’s dictum: the lucid dream is via regia not to the unconscious mind but to world as such.